OVERVIEW OF JURIDICAL LEGAL POSITION OF CHILDREN FROM MARRIAGE SERIES ACCORDING TO ARTICLE 43 ACT NO. 1 YEAR 1974 ABOUT MARRIAGE - Andi Yuliana Karim; Ma’ruf Hafidz; Muh. Rinaldy Bima (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal